Academic Reading Proficiency of Freshmen in the College of Education of DMMMSU-SLUC: Input to the Design of Instructional Modules for English 101 - Uychoco, Dionisio M. (JPAIR Multidisciplinary Research, 2012)
The study described the academic reading proficiency level of incoming college freshmen which served as an input to the design of learning modules. It used a validated 50-item researchermade test and two sets of questionnaires to determine the adequacy of learning activities and the extent of utilization of academic reading strategies by content area teachers. The research found the studentrespondents unprepared for college work given the moderate academic reading proficiency index. Concerned language and content area teachers failed to provide enough learning activities and sufficient opportunity and training in the use of academic reading strategies that will enhance students' level of proficiency in content area reading. It is recommended that topics designed to develop academic reading skills of senior high school students be included in the course content in secondary schools; that English teachers provide more learning activities and experiences expected in content area reading; and that content area teachers become active reading teachers by facilitating comprehension through the use of time-tested academic reading strategies.
Keywords: academic reading strategies; proficiency test; content area reading; instructional materials